Non-smooth model of a frictionless and dry three-dimensional revolute joint with clearance for multibody system dynamics - Cavalieri, Federico José (2018)
Defects in kinematic joints notably influence the relative position and the dynamic response of the bodies in a multibody system. For example, clearance in joints produces impacts that generate wear and/or vibrations which can break a component or generate a drastic life reduction of a mechanical system. In this work, a new element for modeling three-dimensional revolute joints with clearance is proposed. The equations of motion are solved with a non-smooth generalized-α time integration scheme, in which the constraints at velocity and position levels are satisfied exactly without requiring the user to define any penalty parameter. The numerical behavior of the proposed joint is analyzed through four numerical examples where the powerfulness of the proposed methodology is demonstrated.